Análisis de la cartera vencida y su incidencia sobre el patrimonio de las cooperativas de ahorro y crédito segmento tres del Cantón Latacunga en el período 2017 - Pila Yánez, Myriam Rocío (2019)
This research project aims to present the analysis of the overdue portfolio and its impact on the patrimony of the savings and credit cooperatives of three segment, established by Superintendence of Popular and Solidarity Economy, in order to determine the problems caused by the breach of credit obligations granted to the customers. The work will be carried out in the Savings and Credit Cooperatives “Andina Ltda”. And “Sumak Kawsay Ltda”. In the years 2015, 2016, and 2017, which was chosen because of the ease of the information provided by the organizations; it allows to know the problems presented by financial institutions and the breach of credit obligations, which may directly affect the heritage, this through the investigation of the policies and procedures to recover the overdue loan portfolio and the analysis of the financial statements, by means of financial indicators. For the execution of this project it will be necessary to apply methods, techniques and research instruments, procedures that will allow recognizing the possible causes of the breach of credit obligations by the partners. To determine the incidence with the heritage, an analysis of the executed financial statements for 2015, 2016 and 2017 will be carried out. The direct beneficiaries of the project will be conformed of the directors of the designated Savings and Credit Cooperatives of three segment, while the indirect beneficiaries will be formed by the entities that regulate the Ecuadorian Financial System, in this case the Superintendency of Popular and Solidarity Economy, in addition of the students who will develop the research and as a source of information for future research, the contribution of the research will improve and take corrective measures that will help the planning of the managers, focused on generating profits and thus obtain confidentiality with the clients, therefore, it is important because the current situation of the entity will be determined and irregularities detected. To present themselves.